Islamic Accountability Measurement Model: A Demand in Islamic Boarding Schools (Pesantren) - Ramdhansyah, Ramdhansyah; Siregar, Tapi Rumondang Sari; Sriwedari, Tuti; Setiana, Esa (Program Studi Pendidikan Agama Islam, 2026)
This study aims to develop a framework for measuring accountability in Islamic boarding schools (pesantren), adapted from the Islamic accountability measurement instruments used in Islamic financial institutions. This research is crucial in addressing the need to develop Islamic-based accountability measurement instruments applicable to Islamic boarding schools. Data in this study were obtained through questionnaires distributed to parents of students enrolled in Islamic boarding schools in Deli Serdang Regency, who participated as respondents. The analysis involved content validity testing, exploratory factor analysis, and internal reliability assessment to evaluate the proposed construct. The findings identified seven dimensions that may serve as indicators of Islamic accountability, namely amar ma’ruf nahi munkar (commanding good and preventing wrong doing), maslahat ummat (public benefit of the ummah), ‘adala (justice), ihsan (benevolence), amanah (trustworthiness), ikhlas (sincerity), and rahmah (compassion). This research highlights that accountability in Islam is not limited to administrative or procedural duties, but represents a multidimensional framework shaped by ethical, spiritual, and social principles.